Lipopolysaccharides promote a shift from Th2-derived airway eosinophilic inflammation to Th17-derived neutrophilic inflammation in an ovalbumin-sensitized murine asthma model. (28th May 2017) - Zhao, Shengtao; Jiang, Yunqiu; Yang, Xu; Guo, Donglin; Wang, Yijie; Wang, Jun; Wang, Ran; Wang, Changzheng
ABSTRACT: Introduction : The currently available treatments for severe asthma are insufficient. Infiltration of neutrophils rather than eosinophils into the airways is an important inflammatory characteristic of severe asthma. However, the mechanism of the phenotypic change from eosinophilic to neutrophilic inflammation has not yet been fully elucidated. Methods : In the current study, we examined the effect of lipopolysaccharides (LPS) on eosinophilic asthmatic mice sensitized with ovalbumin (OVA), as well as the roles of interleukin (IL)-17A/T helper (Th) 17 cells on the change in the airway inflammatory phenotype from eosinophilic to neutrophilic inflammation in asthmatic lungs of IL-17A-deficient mice. Results: Following exposure of OVA-induced asthmatic mice to LPS, neutrophil-predominant airway inflammation rather than eosinophil-predominant inflammation was observed, with increases in airway hyperresponsiveness (AHR), the IL-17A level in bronchoalveolar lavage fluid (BALF) and Th17 cells in the spleen and in the pulmonary hilar lymph nodes. Moreover, the neutrophilic asthmatic mice showed decreased mucus production and Th2 cytokine levels (IL-4 and IL-5). In contrast, IL-17A knockout (KO) mice exhibited eosinophil-predominant lung inflammation, decreased AHR, mucus overproduction and increased Th2 cytokine levels and Th2 cells. Conclusion : These findings suggest that the eosinophilic inflammatory phenotype of asthmatic lungs switches to the neutrophilic phenotype following exposure to LPS. The change in the inflammatory phenotype is strongly correlated with the increases in IL-17A and Th17 cells.